Do personality traits predict individual differences in excitatory and inhibitory learning? - He, Z.; Cassaday, Helen J.; Bonardi, Charlotte; Bibby, Peter A. (Frontiers, 2013)
Conditioned inhibition (CI) is demonstrated in classical conditioning when a stimulus is used to signal the omission of an otherwise expected outcome. This basic learning ability is involved in a wide range of normal behavior – and thus its disruption could produce a correspondingly wide range of behavioral deficits. The present study employed a computer-based task to measure conditioned excitation and inhibition in the same discrimination procedure. CI by summation test was clearly demonstrated. Additionally summary measures of excitatory and inhibitory learning (difference scores) were calculated in order to explore how performance related to individual differences in a large sample of normal participants (n = 176 following exclusion of those not meeting the basic learning criterion). The individual difference measures selected derive from two biologically based personality theories, Gray’s (1982) reinforcement sensitivity theory and Eysenck and Eysenck (1991) psychoticism, extraversion, and neuroticism theory. Following the behavioral tasks, participants completed the behavioral inhibition system/behavioral activation system (BIS/BAS) scales and the Eysenck personality questionnaire revised short scale (EPQ-RS). Analyses of the relationship between scores on each of the scales and summary measures of excitatory and inhibitory learning suggested that those with higher BAS (specifically the drive sub-scale) and higher EPQ-RS neuroticism showed reduced levels of excitatory conditioning. Inhibitory conditioning was similarly attenuated in those with higher EPQ-RS neuroticism, as well as in those with higher BIS scores. Thus the findings are consistent with higher levels of neuroticism being accompanied by generally impaired associative learning, both inhibitory and excitatory. There was also evidence for some dissociation in the effects of behavioral activation and behavioral inhibition on excitatory and inhibitory learning respectively.